STRATEGI PENINGKATAN KREATIVITAS ANAK MELALUI PENDEKATAN PEMBELAJARAN QUANTUM GAMES DI RAUDHATUL ATHFAL IBNU SINA PALEMBANG - Sartika, Dewi (Conciencia, 2019)
Creativity is the ability to create new ones and can be applied in problem solving. Strategies in developing children's creativity need to review four aspects of creativity, namely "personal, push, process and product." Learning that can lead to motivation and can improve student learning achievement that makes a learning process more meaningful, so students will be able to understand the material taught and be able to convert playing energy into a light of intelligence called quantum games learning. To express this side this research formulates the problem as follows: First, How is the implementation of the Quantum Games model in Early Childhood Learning at Raudhatul Athfal Ibn Sina; Second, how the creativity of Early Childhood in Raudhatul Athfal Ibn Sina; Third, how to increase the creativity of students after the implementation of Quantum Games Learning at Raudhatul Athfal Ibn Sina. This study uses a qualitative field approach that is descriptive qualitative, its analysis through the stages of data reduction, data presentation, and conclusion drawing. Research results in the field have been found: First, the development of the implementation of the Quantum Games model in early childhood learning at Ibn Sina Palembang's Raudhatul Athfal still refers to the National curriculum, the language of instruction is Indonesian and the point is children are taught to play with the aim of changing children's energy smarter in thinking. Second, Early Childhood Creativity in Raudhatul Athfal Ibnu Sina Palembang, with this learning can be seen that children are more active in learning, and with this learning the child looks very excited in playing and learning among his friends trying to invite students to participate more in the teaching and learning process, is not limited to being a passive listener, but also seeing, discussing it, practicing it, and teaching it to other children. Third, the effect of the implementation of the Quantum Games Learning model on the creativity of early childhood at Raudhatul Athfal Ibnu Sina Palembang, that children appear to experience gradual changes which is certainly more than before because before applying qauntum games to children the learning spirit is lacking, qauntum learning is implemented children's games change in learning as they look very enthusiastic and ask questions and are fun for children.